A proteção da família no Regime Geral de Previdência Social: uma análise a partir do benefício de pensão por morte - Maia, Fábio Vinícius (2020)
This master's dissertation is entitled 'Family Protection in the General Social Security Scheme – an Analysis from the Perspective of the Survivor’s Pension Social Benefit”. It addresses the legal mechanism which regulates the survivor’s pension highlighting the deep changes that have occurred in family law since the Federal Constitution of 1988. That Constitution broke with a past that advocated a unique family format – which had a matrimonial, patriarchal, patrimonial, and hierarchical profile – by recognizing and giving protection to other forms of family composition, such as the stable union deed and the single-parent family, as well as establishing equal rights and duties between men and women before marriage. These changes that took place through the legislature and even the judiciary paved the way for other innovations. They had an impact on social security, being the most important, the one that redefines the list of eligible survivors of the insured person before the Social Security.The aim of this paper is to analyze, in its entirety, the protection of the family offered by the Brazilian Social Security, comprising social risks. Special focus is given to the risk of death, which involves the social benefit of survivor’s pension, granted to eligible survivors on the death of the insured person